Defense Against Bioterror
DOI: 10.1007/1-4020-3384-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bioaerosol Alarming Detector

Abstract: Abstract:Although banned by the BTWC in 1972, biological warfare agents continue to be a threat to military and public health. Countermeasures can only be effective if rapid detection and reliable identification techniques are in place. TNO Prins Maurits Laboratory, and Delft University of Technology and Bruker-Daltonik (Germany) are developing an bioaerosol alarm detector, based on fluorescence pre-selection, Aerosol Time-of-Flight Mass Spectrometry (ATOFMS) and Matrix-Assisted Laser Desorption/Ionization (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This matrix effect in the laser desorption studies is still misinterpreted and under discussion [8,40]. Thomson et al (1997) suggested that the energetic level necessary to obtain an ion production of a constituent strongly depends on other compounds present within the particle under analysis [39].…”
Section: Discussionmentioning
confidence: 99%
“…This matrix effect in the laser desorption studies is still misinterpreted and under discussion [8,40]. Thomson et al (1997) suggested that the energetic level necessary to obtain an ion production of a constituent strongly depends on other compounds present within the particle under analysis [39].…”
Section: Discussionmentioning
confidence: 99%